2021
DOI: 10.3389/fped.2021.568755
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Neurobiological Vulnerabilities of the Hospitalized Preterm Infant and Relevant Non-pharmacological Pain Mitigation Strategies

Abstract: Background: Preterm pain is common in the Neonatal Intensive Care Unit (NICU), with multiple invasive procedures occurring daily.Objective: To review the psychosocial and neurobiological vulnerabilities of preterm infants and to provide an updated overview of non-pharmacological strategies for acute procedural pain in hospitalized preterm infants.Methods: We utilized a narrative review methodology, which also included a synthesis of key pieces of published systematic reviews that are relevant to the current wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 103 publications
(138 reference statements)
0
7
0
2
Order By: Relevance
“…Studies show that unrelieved acute pain can affect the neurodevelopment of neonates, producing motor, cognitive, and behavioural alterations [ 9 , 10 ]. It is therefore necessary to modify clinical practice and attenuate stimuli in order to guarantee the comfort of these patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that unrelieved acute pain can affect the neurodevelopment of neonates, producing motor, cognitive, and behavioural alterations [ 9 , 10 ]. It is therefore necessary to modify clinical practice and attenuate stimuli in order to guarantee the comfort of these patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm infants in the NICU are subjected to invasive medical therapies on a regular basis in order to prevent, diagnose, and treat severe illnesses (Coviello et al., 2018 ). Furthermore, it was demonstrated that they were exposed to an average of 12–17 procedures daily in the NICU (Shiff et al., 2021 ). Therefore, identifying interventions that minimise pain levels with minor side effects is extremely urgent for healthcare providers and researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have indicated that multiple acute pain procedures in NICUs can result in “a chronically painful state” for preterm infants [ 64 , 65 ], which is detrimental to pain recovery, neurodevelopment, and psychosocial health [ 66 ]. Non-pharmacological interventions for managing pain have gained significant attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological interventions for managing pain have gained significant attention in recent years. However, the effectiveness of these interventions has not yet been clear and remains an area of ongoing research [ 66 , 67 ]. Based on this, this meta-analysis compared their efficacy and found that OS + NNS, facilitated tucking and auditory intervention were relatively more effective.…”
Section: Discussionmentioning
confidence: 99%